Website credibility factors in influencing user engagement - Saiful Bahry, Farrah Diana; Masrom, Maslin; Masrek, Mohamad Noorman; Amran, Noraizan (Universiti Teknologi MARA, Kedah, 2017)
Website content plays a crucial role in attracting website user to keep user engage on the website. The aim of the research was to investigate on website credibility factors focuses for information-driven website such as municipal electronic government websites in influencing website user engagement. The proposed framework of website credibility factors in influencing user engagement was derived as previous studies were lack in assessing whole aspect of website credibility and also scarce in incorporate it with user engagement. The prominence of website content elements and features and acted as credibility cues and all verified content elements and design features have been encapsulated as part of the scale items in appropriate adapted variable in survey instrument development. The study employed quantitative approach by using survey questionnaire as instrument which adopted and adapted from previous researchers. The survey questionnaire was distributed among website users for ten (10) municipal websites within Klang Valley which aged from eighteen years old and above, using online and printed questionnaire. In analyzing, descriptive data analysis and structural equation modeling technique were used in order to answer the research objectives. Findings of this study are proving that mostly all website credibility factors have a relationship on user engagement. The research model is suite for information-driven websites and a value-aided guideline for web content management practice that conforming to website credibility also has been proposed. The study benefitedthe web content management practitioners and web developers in identifying which website content element and design features that can act as credibility cues in informationdriven website in which influence user engagement.